2014
DOI: 10.1111/ijn.12281
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and job satisfaction among new graduate nurses during the first year of employment in Taiwan

Abstract: Nurse graduates are leaving their first employment at an alarming rate. The purpose of this study was to explore the relationships between job stress, job satisfaction and related factors over time among these nurses. This study applied a longitudinal design with three follow-ups after nurse graduates' first employment began. Using convenience sampling, participants were 206 new graduates from a university. The Work Environment Nursing Satisfaction Survey and the Clinical Stress Scale were used in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
6
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 20 publications
4
54
6
3
Order By: Relevance
“…Furthermore, no difference was observed in job satisfaction score between score groups. These results are different from those of previous studies [33,34] claiming that job stress and job satisfaction had either a negative or a positive correlation. To determine the systematic relationship among these variables, it will be necessary to examine the relationship among specific aspects of job stress and job satisfaction in studies that include larger samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, no difference was observed in job satisfaction score between score groups. These results are different from those of previous studies [33,34] claiming that job stress and job satisfaction had either a negative or a positive correlation. To determine the systematic relationship among these variables, it will be necessary to examine the relationship among specific aspects of job stress and job satisfaction in studies that include larger samples.…”
Section: Discussioncontrasting
confidence: 99%
“…In a longitudinal study by Cheng et al . (), nurses who worked 12‐hour shifts reported significantly higher job satisfaction than nurses working 8‐hour shifts. In contrast, Šimunić and Gregov () found 12‐hour shifts to be associated with lower cognitive‐affective job satisfaction compared with nurses working morning shifts.…”
Section: Resultsmentioning
confidence: 87%
“…However, in direct contrast to this study, Cheng et al . () found nurses working 12‐hour shifts reported less job stress than nurses working 8‐hour shifts. One study found fixed shift nurses had higher anxiety and social dysfunction compared with rotating shift nurses (Ardekani et al .…”
Section: Resultsmentioning
confidence: 99%
“…Job satisfaction can be a source of health, but the job dissatisfaction can lead to impairments in physical, social and mental health and cause problems at work. (20) First shift workers had high levels of absenteeism. Study involving workers in the United States showed that 30.2% of the sample was diagnosed with metabolic syndrome, and this showed higher rates of absenteeism compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%